PENGARUH KEMUDAHAN PENGGUNAAN DAN RISIKO KEAMANAN TERHADAP KEPUTUSAN BERTRANSAKSI MENGGUNAKAN QRIS DI KOTA JAMBI - Ramadan, Akmal; Anggraeni, Lidya; Rohana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of perceived ease of use and security risk on transaction decisions using the Quick Response Code Indonesian Standard (QRIS) among Generation Z and Baby Boomers in Jambi City. The study employed a quantitative approach using primary data collected through questionnaires. Data were analyzed using multiple linear regression, t-test, F-test, coefficient of determination, and Mann-Whitney test. The results show that perceived ease of use has a positive and significant effect on QRIS transaction decisions, while security risk has no significant partial effect. Simultaneously, perceived ease of use and security risk significantly affect transaction decisions. In addition, there are differences between Generation Z and Baby Boomers in perceived ease of use and transaction decisions, but no significant difference in security risk. These findings indicate that improving ease of use and strengthening transaction security remain important to increase public acceptance of QRIS.